Microbial biotechnology in agriculture and aquaculture - Ray, Ramesh C. (Enfield, (NH) : Science Publishers, 2005)
Annotation In agriculture, microbial biotechnology covers a wide array of subjects ranging from biofertilizers to biological control of pests and diseases; from biological N 2 -fixation to lignocellulose degradation; from production of biomass and biofuels to genetically engineered plants. Similarly, microbial biotechnology in aquaculture touches several aspects such as biofilms, bioprocessing of biomaterials (metabolites, enzymes, proteins, exopolysaccharides, etc.), application of biofertilizers, probiotics, bio-remediation of contaminated water, etc. This book is an attempt to highlight the significant aspects of the vast subject area like application of microbial biotechnology in agriculture and aquaculture.
""14. Use of Microbes in Managing Post-harvest Crop Residues: Sugarcane Residue as a Case Study""""15. Microbial Technology for Bioethanol Production from Agricultural and Forestry Wastes ""; ""Index""
Includes bibliographical references.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Microbial biotechnology; Agricultural biotechnology; Aquaculture; Electronic books